2013
DOI: 10.2147/ibpc.s34803
|View full text |Cite
|
Sign up to set email alerts
|

A review of the gastrointestinal therapeutic system (GITS) formulation and its effectiveness in the delivery of antihypertensive drug treatment (focus on nifedipine GITS)

Abstract: Hypertension treatment guidelines do not discriminate within drug classes and, furthermore, do not consider whether or not all of the formulations of any given drug licensed for once-daily administration can be considered to be therapeutically interchangeable. This article focuses on this issue with respect to nifedipine and the development of the gastrointestinal therapeutic system (GITS) formulation. Nifedipine GITS is regarded as the gold standard once-daily formulation of nifedipine and, as such, it is ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Nifedipine and candesartan cilexetil are both effective monotherapies for lowering BP 16, 17, 18, 19. The nifedipine GITS formulation offers, in addition, the advantage of controlled drug release, making it suitable for once‐daily administration, and an observational study suggests that candesartan reduces the risk of cardiovascular disease and heart failure in comparison with another angiotensin receptor blocker (ARB), losartan 16, 18.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nifedipine and candesartan cilexetil are both effective monotherapies for lowering BP 16, 17, 18, 19. The nifedipine GITS formulation offers, in addition, the advantage of controlled drug release, making it suitable for once‐daily administration, and an observational study suggests that candesartan reduces the risk of cardiovascular disease and heart failure in comparison with another angiotensin receptor blocker (ARB), losartan 16, 18.…”
mentioning
confidence: 99%
“…[16][17][18][19] The nifedipine GITS formulation offers, in addition, the advantage of controlled drug release, making it suitable for once-daily administration, and an observational study suggests that candesartan reduces the risk of cardiovascular disease and heart failure in comparison with another angiotensin receptor blocker (ARB), losartan. 16,18 A placebo arm was included in DIS-TINCT in accordance with the International Conference on Harmonisation guideline for evaluation of fixed-dose combination products for the treatment of hypertension and similar to other multifactorial trials of combination antihypertensive therapies. [20][21][22][23] DIS-TINCT demonstrated that initial combination therapy with nifedipine GITS/candesartan cilexetil was more effective in lowering BP and meeting target BP goals (SBP <140 and DBP <90 mm Hg) vs respective monotherapies at the same doses in participants with hypertension.…”
mentioning
confidence: 99%
“…Nifedipine is a calcium channel blocker given for treatment of hypertension and chronic angina, with frequent dosing in the past [ 3 ]. An extended release formulation of nifedipine was developed to achieve once-daily dosing using the gastrointestinal therapeutic system (GITS) [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…The primary goal of antihypertensive therapy is to control blood pressure and reduce the long-term risk of cardiovascular morbidity and mortality. Different classes of medication are available for the management of hypertension 4,5,6 . Nifedipine [Dimethyl-2,6-methyl-4-( 2-nitrophenyl)-1, 4-dihydropyridine-3, 5-dicarboxylate] (Fig 1) is a calcium channel blocking agent which is commonly employed in the management of systemic hypertension and angina pectoris 7 .…”
Section: Introductionmentioning
confidence: 99%
“…°C. Aliquot samples of 10 ml were withdrawn at pre scheduled intervals(1,3,4,6, and 12 h) and replaced with an equal volume of fresh dissolution medium which was kept at 37±0.5 °C to maintain sink condition. Each filtered sample was analyzed for drug content at  max of 329 nm using a UV/Visible Spectrophotometer.…”
mentioning
confidence: 99%